Pengaruh Kinerja Keuangan dan Penerapan GCG terhadap Potensi Kebangkrutan pada PT Bank Muamalat Indonesia Tbk - Jihan Humaira; Benny Barnas; Kristianingsih Kristianingsih (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to determine the effect of financialoperformance as proxied by ROA, BOPO, CAR and FDR as welloas the implementation of good corporate governance proxiedoby the Sharia Supervisory Board on financial distress (Modified Altman Z-Score) at Bank Muamalat 2008-2018. This research method uses a case study method with secondary data in the form of quarterly financial reports and GCG reports issued by PT Bank Muamalat Indonesia Tbk. for the period 2008-2018, data obtained from theoFinancialoServices Authority andoother data related to the subject and object oforesearch. This study uses the Multiple Linear Regression method with the help of Software Statistic Eviews 9. From this study, the results show that ROA has no effect on financial distress, BOPO has no effect on financial distress, CAR has a significant positive effect on financial distress, FDR has a significant negative effect on financial distress, and GCG has no effect on financial distress.